Ottoman Civilization and Its Impact in Contemporary Malaysia: An Evaluation - Gokaru, Shuaibu Umar; Mohd Nor, Mohd Roslan; Abdul Hamid, Faisal @ Ahmad Faisal (Journal of Al-Tamaddun, 2023)
The Ottoman Empire is a multi-cultural and multi-lingual empire that influenced not only the Muslim Nations but even non-Muslims, particularly in Europe. This might have been achieved because of the direct and indirect connection between the Ottomans and the nations. In this regard, Malaysia is not an exception. Although various authors and academics contributed to analysing issues relating to the connection between the Malay Archipelago and the Ottomans, particularly on diplomatic relations, the details of the impacts of Ottoman civilizations in contemporary Malaysia have been largely overlooked. This idea generated interest in the topic. This research, therefore, intends to evaluate the impact of Ottoman civilizations on religion, education, science, and technology in contemporary Malaysia. The research uses qualitative methods in the form of historical research. The usage of documentary method is used for data collection and evaluation. The findings reveal that Ottoman civilization had a lasting impact on contemporary Malaysia, especially in education and religion in which a special prayer is recited for the well-being of Sultan at the end of the Khutbah of every Jumu’ah Prayer. In addition, the findings show that the impact of Ottoman civilization on contemporary Malaysia is exemplified in science and technology, as well as the architectural building of the Mosque in which Masjid Wilayah, Kuala Lumpur Mosque is called a Turkish Mosque because of its design which has huge resemblance to the Masjid Hagia Sophia in Istanbul and International Islamic University, Malaysia (IIUM) represents the Ottoman symbols. On the other hand, Johor, a state in the south of Malaysia represents the Ottoman civilization more than any ex-provinces of the Ottoman territories. Finally, the findings indicate that the provision of conveniences (toilets) in public places, in Malaysian Mosques, Markets, and Supermarkets whether owned by Muslims or non-Muslims, are all influenced by the Ottoman civilizations. This research, therefore, recommends that researchers should further look at other aspects within the city and its outskirt to identify the impact of the Ottoman civilization on contemporary Malaysia.